Are Chinese nanoscience citation curves converging towards their American counterparts? - Hu, Xiaojun; Rousseau, Ronald (Malaysian Journal of Library and Information Science, 2017)
Hu, X., & Rousseau, R. (2013). Are Chinese nanoscience citation curves converging towards their American counterparts. Malaysian Journal of Library & Information Science, Vol.18, no. 3: 49-56. We investigate if the shape of citation curves of Chinese publications in the field of nanoscience and nanotechnology converge to those of America and find that they, indeed, do. The used approach is size independent and, hence, can be used to compare not only large countries but also countries of intermediate size.